Beyond Inclusion Worklife Interconnectedness, Energy, and Resilience in Organizations - Smith, J. Goosby; Lindsay, Josie Bell.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Beyond Inclusion adopts a holistic and systems view of the organization, presents a behavioral model of organizational inclusion based upon research with thousands of employees, and discusses elements of organizational design that need to be adjusted to create, nurture, and sustain an inclusive culture.
Keywords: Business ethics; Organization; Planning; Economic sociology; Office management; Behavioral economics; Manpower policy; Business Ethics; Organization; Organizational Studies, Economic Sociology; Office Management; Behavioral/Experimental Economics; Human Resource Development